2018
DOI: 10.30827/reugra.v25i0.106
|View full text |Cite
|
Sign up to set email alerts
|

Intervención de teatro de sombras en un caso con Necesidades Educativas Especiales por Trastorno de Espectro Autista

Abstract: Este artículo forma parte de una tesis doctoral que investiga la mejora de alumnos con Necesidades Educativas Especiales (NEE) a través de la intervención de medios innovadores procedentes de las Artes. Este artículo se centra en el caso de un menor con Trastornos de Espectro Autista (TEA) que presenta dificultades en el control postural, en el lenguaje espontáneo, baja autoestima, escasa conciencia corporal y dificultades en las relaciones sociales. Se diseña y aplica una intervención de teatro de sombras que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The sample sizes in the reviewed studies varied, ranging from 1 person [27] to 77 persons [28]. All studies reported an improvement in social-emotional functioning, self-esteem, emotion management, empathy, and listening as well as a decrease in stress and anxiety and an increase in body awareness, communicative intention, adaptive skills, communication, and social interaction through different theatrical techniques.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample sizes in the reviewed studies varied, ranging from 1 person [27] to 77 persons [28]. All studies reported an improvement in social-emotional functioning, self-esteem, emotion management, empathy, and listening as well as a decrease in stress and anxiety and an increase in body awareness, communicative intention, adaptive skills, communication, and social interaction through different theatrical techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Three of the articles analyzed focused on theatrical experiences in early care centers to test whether the consolidation of social skills in children with ASD was more effective through theatrical play than through traditional learning methods [27,36,37]. The three interventions in these studies involved working on social interaction, body perception, peer relationships, courtesy rules, understanding of instructions, rhythm and imitation, recognition of emotions, representation of emotions, and association of emotions with circumstances.…”
Section: Resultsmentioning
confidence: 99%